SISTEM INFORMASI SURAT PEMBERITAHUAN PERKEMBANGAN HASIL PENYELIDIKAN (SP2HP) DI POLRES TANJUNG JABUNG TIMUR: information system, SP2HP, website - Mulyati, Sri; Amelia, Ferina (LP2M Universitas Nurdin Hamzah, 2018)
Web-based SP2HP information system is an application that can help the police in terms of the field of crime in providing information about SP2HP to website visitors and helping people get SP2HP online.This system is one of the technologies that is growing very rapidly at this time. Technological developments accompanied by the development of science in all fields pushed almost all institutions into computer-based technology. The development of technology accompanied by the development of science requires that all things be done quickly and accurately, especially in an Tanjung Jabung Timur police station, especially in the field of police. Because in this field it serves cases that discuss the events that occur in the community. To improve the efficiency and effectiveness of work, especially in the letters section, a web was made that discussed the